Inequality and the Marriage Gap - Nawid Siassi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Marriage is one of the most important determinants of economic prosperity, yet most existing theories of inequality ignore the role of the family. This paper documents that the cross-sectional distributions of earnings and wealth display a high degree of concentration, even when disaggregated into single and married households. At the same time, there is a large marriage gap: married people earn on average 27 percent more income, and they hold 34 percent more net worth. To account for these empirical facts, I develop a theory based on an otherwise standard incomplete-markets OLG model with ex-ante identical agents, who (i) are randomly selected into single or married households at the beginning of their economic lives; (ii) face uninsurable labor market risk henceforth; (iii) and make Pareto-efficient decisions if married. In a calibrated version of the model, I show that positive assortative matching, an effective tax bonus for married couples and directed bequests are key to explaining the marriage gap in earnings and wealth. A policy experiment of moving from joint tax filing for married couples to separate filing yields output and welfare gains.
Keywords: D31; E21; D91; 330